자색고구마로부터 분리한 안토시아닌 분획물의 고지방식이로 유도된 인슐린 저항성과 간 지질 축적 개선 효과 - 남송이(Song Yee Nam); 장환희(Hwan Hee Jang); 김정봉(Jung Bong Kim); 이성현(Sung Hyun Lee); 이영민(Young Min Lee) (東아시아食生活學會誌, 2016)
Anthocyanins, a class of flavonoids, are natural water-soluble pigments, mainly found in vegetables and fruits. Anthocyanins have attractive pharmacological activities, such as anti-oxidant, anti-inflammatory, anti-cancer, and anti-diabetic effects. The purpose of this study was to investigate the inhibitory effects of the anthocyanin-rich fraction (ANF) from purple sweet potato on high fat diet-induced insulin resistance and hepatic steatosis. C57BL/6J mice were assigned to the following groups (n=8 per group): normal fat diet (NF); high fat diet (HF); high fat diet with ANF 50mg/kg (ANF50). Normal fat or high fat diets were fed for a total of 17 weeks, and ANF was orally administrated for 8 weeks (from 10 to 17 weeks, five times/week). In our results, there were no significant differences in body weight, food intake, and tissue weight upon ANF supplementation. The levels of serum triacylglycerol, total-cholesterol, and glucose were also not affected by ANF supplementation. However, ANF supplementation significantly decreased serum insulin and HOMA-IR levels as well as prevented hepatic fat accumulation in high fat-fed mice. These results show that ANF may be beneficial for improving high fat-induced insulin resistance and protecting against development of hepatic steatosis.